The harmonic oscillator is an interesting system particularly because
it has a close relationship with photons, which we will explore later.
As we saw when we looked at a coherent state, it had the same \(\Delta x\) and \(\Delta p\) of the minimal uncertainty
ground state. Can we do better?
Well, we certainly cannot reduce the product of \(\Delta x\) and \(\Delta p\), but we can trade off the
uncertainty—for example, if I find a state where \(\Delta x\) is multiplied by \(e^{-r}\) and \(\Delta p\) by \(e^{r} (r \text{ is real})\), then we can
reduce the uncertainty in \(x\) at the
expense of raising it for \(p\) when
\(r \geq 0\). But if we want to measure
\(x\) then this may be advantageous. At
the very least, it looks like by changing \(r\) from \(-\infty\) to \(+\infty\), we could continuously change
from momentum eigenstates to position eigenstates, just by changing a
parameter. That would be cool. (Indeed, it does work).
Another exciting thing is working with coherent states gives us more to
exercise with our 5 operator identities. Practice makes perfect!
The operator for squeezing can be thought of as a generalization of the displacement operator from being a linear function of \(\hat{a}\) and \(\hat{a}^{\dagger}\) to a quadratic one.
We use \(\hat{S}(\xi, \eta)=\exp
\left[-\frac{\xi}{2} (\hat{a}^{\dagger})^{2}+\frac{i
n}{2}\left(\hat{a}^{\dagger}\hat{a} + \hat{a}
\hat{a}^{\dagger}\right)+\frac{\xi^{*}}{2}
\hat{a}^{2}\right]\)
where \(\xi\) can be complex, but \(\eta\) is always real. Why the odd looking
choices of parameters? We want \(\hat{S}\) to be unitary. But \[\begin{aligned}
& (\hat{S}(\xi, \eta))^{\dagger}=\exp \left[-\frac{\xi^{*}}{2}
\hat{a}^{2}-\frac{i\eta}{2}\left(\hat{a}^{\dagger} \hat{a}+\hat{a}
\hat{a}^{\dagger}\right)+\frac{\xi}{2}(\hat{a}^{\dagger})^{2}\right] \\
& =\hat{S}(-\xi,-\eta)=\exp \left[-\left(-\frac{\xi}{2}
(\hat{a}^{\dagger})^{2}+\frac{i \eta}{2}\left(\hat{a}^{\dagger}
\hat{a}+\hat{a}\hat{a}^{\dagger}\right)+\frac{\xi^*}{2}
\hat{a}^{2}\right)\right].
\end{aligned}\] Now, we recall \(\exp
(\hat{A}) \exp (-\hat{A})=1\), for any operator \(\hat{A}\). Hence \[(\hat{S}(\xi, \eta))^{\dagger}=(\hat{S}(\xi,
\eta))^{-1}.\] That implies \(\hat{S}\) is unitary!
Since \(\hat{S}\) has a quadratic in
the exponent, it is like we are controlling the kinetic energy and the
potential energy. For example, if we make the potential more confining
and narrow, the wave function should be squeezed closer to the origin.
This is a way to think about the procedure.
Let’s think of \(\hat{S}(\xi, \eta)\) as being a unitary transformation. Then all operators are transformed like \(\hat{O} \rightarrow \hat{U}^{\dagger} \hat{O} \hat{U}\) or
\[\hat{a} \rightarrow \hat{S}^{\dagger}(\xi, \eta) \hat{a} \hat{S}(\xi, \eta)=\underbrace{\hat{S}(-\xi, -\eta) \hat{a} \hat{S}(\xi, \eta)}_{\text {Hadamard! }}\]
So \[\quad \hat{a} \rightarrow
\hat{a}-[(-\frac{\xi}{2} (\hat{a}^{\dagger})^2+\frac{i
\eta}{2}\left(\hat{a}^{\dagger}\hat{a}+\hat{a}
\hat{a}^{\dagger}\right)+\frac{\xi^{*}}{2} \hat{a}^{2}),
\hat{a}]\]
\[+\frac{1}{2}[(-\frac{\xi}{2}(\hat{a}^{\dagger})^{2}+\frac{i
\eta}{2}(\hat{a}^{\dagger}\hat{a} + \hat{a}\hat{a}^{\dagger}) +
\frac{\xi^{*}}{2}\hat{a}^{2}),[(-\frac{\xi}{2}(\hat{a}^{\dagger})^{2}+\frac{i
\eta}{2}(\hat{a}^{\dagger}\hat{a} + \hat{a}\hat{a}^{\dagger}) +
\frac{\xi^{*}}{2}\hat{a}^{2}),\hat{a}]]\\
+\cdots\] \[\begin{aligned}
=\hat{a}- (\xi \hat{a}^{\dagger} - i \eta
\hat{a})+\frac{1}{2}(\xi(\xi^{*}\hat{a} + i \eta \hat{a}^{\dagger}) - i
\eta (\xi\hat{a}^{\dagger} - i \eta \hat{a})) +\cdots\\
=\hat{a}- (\xi \hat{a}^{\dagger} - i \eta
\hat{a})+\frac{1}{2}(|\xi|^{2}-\eta^{2}) \hat{a}+\cdots
\end{aligned}\] since the \(\hat{a}^{\dagger}\) term vanishes. This
actually allows us to perform the infinite sum, because the nested
commutators repeat.
\[\begin{aligned}
\hat{a} \rightarrow \hat{a} &
\left(1+\frac{1}{2}\left(|\xi|^{2}-\eta^{2}\right)+\frac{1}{4!}|\xi|^{2}-\left.\eta^{2}\right)^{2}+\cdots\right)
\\
& -\left(\xi \hat{a}^{\dagger}-i \eta
\hat{a}\right)\left(1+\frac{1}{3!}\left(|\xi|^{2}-\eta^{2}\right)+\frac{1}{5!}\left(|\xi|^{2}-\eta^{2}\right)^{2}+\cdots\right).
\end{aligned}\]
Now use the hyperbolic trigonometric functions \[\begin{aligned} & \cosh y=\sum_{m=0}^{\infty} \frac{y^{2 m}}{(2 m)!} \quad \text{and}\quad\sinh y=\sum_{m=0}^{\infty} \frac{y^{2 m+1}}{(2 m +1)!}, \\ & \hat{a} \rightarrow \hat{a} \cosh \sqrt{|\xi|^{2}-\eta^{2}}-\frac{\left(\eta \hat{a}^{\dagger}-i \eta \hat{a}\right)}{\sqrt{|\xi|^{2}-\eta^{2}}} \sinh \sqrt{|\xi|)^{2}-\eta^{2}} \\ \end{aligned}\] Hence \[\boxed{ \begin{aligned} \hat{S}^{\dagger}(\xi, \eta) \hat{a} \hat{S}(\xi, \eta) & =\hat{a}\left[\cosh \sqrt{|\xi|^{2}-\eta^{2}}+\frac{i \eta}{\sqrt{ |\xi|^{2}-\eta^{2}}} \sinh \sqrt{|\xi|^{2}-\eta^{2}}\right] \\ & -\hat{a}^{\dagger} \frac{\xi}{\sqrt{|\xi|^{2}-\eta^{2}}} \sinh \sqrt{|\xi|^{2}-\eta^{2}} \end{aligned} }\]
Taking the Hermitian conjugate gives us \[\boxed{ \begin{aligned} \hat{S}^{\dagger}(\xi, \eta) \hat{a}^{\dagger} \hat{S}(\xi, \eta)= & -\hat{a} \frac{\xi^{*}}{\sqrt{|\xi|^{2}-\eta^{2}}} \sinh \sqrt{|\xi|^{2}-\eta^{2}} \\ & +\hat{a}^{\dagger}\left[\cosh \sqrt{|\xi|^{2}-\eta^{2}}-\frac{i \eta^{*}}{\sqrt{|\xi|^{2} -\eta^{2}}} \sinh \sqrt{|\xi|^{2}-\eta^{2}}\right] \end{aligned} }\]
You may want to look back at what we derived for similar expressions
with Pauli matrices. These relations resemble those, but are not
identical.
We define \(\hat{S}(\xi,
\eta)|0\rangle=|\xi, \eta\rangle=\) "squeezed vacuum
state".
Then \(\langle \xi, \eta| \hat{x}|\xi,
\eta\rangle=\sqrt{\frac{\hbar}{2 m \omega_{0}}}\langle 0|
\hat{S}^{\dagger}(\xi, \eta)\left(\hat{a}+\hat{a}^{\dagger}\right)
\hat{S}(\xi, \eta)|0\rangle\)
Let \[\boxed{ \kappa=\cosh
\sqrt{(\xi)^{2}-\eta^{2}}+\frac{i \eta}{\sqrt{|\xi|^{2}-\eta^{2}}} \sinh
\sqrt{|\xi|^{2}-\eta^{2}}\quad
\lambda=\frac{\xi}{\sqrt{(\xi)^{2} \eta^{2}}} \sinh
\sqrt{|\xi|^{2}-\eta^{2}}}\] Then \(\hat{S}^{\dagger} \hat{a} \hat{S}=\kappa
\hat{a}-\lambda \hat{a}^{\dagger} \quad \text{and}\quad\hat{S}
\hat{a}^{\dagger} \hat{S}=-\lambda^{*} \hat{a}+\kappa^{*}
\hat{a}^{\dagger}\). So \[\begin{aligned}
&\langle\xi \eta| \hat{x}|\xi \eta\rangle=\sqrt{\frac{\hbar}{2 m
\omega_{0}}}\langle 0|(\kappa \hat{a}-\lambda
\hat{a}^{\dagger}-\lambda^{*} \hat{a}+\kappa^{*} \hat{a}^{\dagger})|
0\rangle=0, \\
&\text { since } \hat{a}|0\rangle=0 \text { and }\langle 0|
\hat{a}^{\dagger}=0. \\
& \langle \xi \eta| \hat{x}^{2} | \xi \eta\rangle=\frac{\hbar}{2 m
\omega_{0}}\langle 0|\big( (\kappa-\lambda^{*})^{2}
\hat{a}^{2}+(\kappa-\lambda^{*})(\kappa^{*} -\lambda) \hat{a}
\hat{a}^{\dagger} \\
& +(\kappa^{*}-\lambda)(\kappa-\lambda^{*}) \hat{a}
\hat{a}^{\dagger}+(\kappa^{*}-\lambda)^{2}
(a^{\dagger})^{2}\big)|0\rangle \\
& =\frac{\hbar}{2 m \omega_{0}}(\kappa -
\lambda^{*})(\kappa^{*}-\lambda)=\frac{\hbar}{2 m
\omega_{0}}(|\kappa|^{2}-2 \operatorname{Re} \kappa \lambda+|
\lambda|^{2}) \\
& \langle \xi \eta| \hat{p} | \xi \eta)=\sqrt{\frac{\hbar m
\omega_{0}}{2}} \langle 0| \big(\kappa \hat{a}-\lambda
\hat{a}^{\dagger}+\lambda^{*} \hat{a}-\kappa^{*}
\hat{a}^{\dagger}\big)|0\rangle =0\\
& \langle\xi \eta| \hat{p}^{2}|\xi \eta\rangle=-\frac{\hbar m
\omega_{0}}{2} \langle 0 |\big((\kappa+\lambda^{*})^{2}
\hat{a}^{2}-(\kappa+\lambda^{*})(\kappa^{*}+\lambda)(\hat{a}
a^{\dagger}+\hat{a}^{\dagger}\hat{a}) \\
& +(\kappa^{*}+\lambda)^{2} (\hat{a}^{\dagger})^{2}\big)|0\rangle \\
& =\frac{\hbar m
\omega_{0}}{2}(\kappa+\lambda^{*})(\kappa^{*}+\lambda)=\frac{\hbar m
\omega_{0}}{2}(|\kappa|^{2}+2 \operatorname{Re} \kappa
\lambda +|\lambda|^{2})
\end{aligned}\] Examine for a special case of \(\eta=0, \quad \xi=r e^{i \phi}\). Then
\(\kappa=\cosh r \quad
\text{and}\quad\lambda=\sinh r e^{i \phi}\), so
\[\begin{aligned} (\Delta x)_{re^{ i \phi}, 0}^{2} & =\frac{\hbar}{2 m \omega_{0}}\left(\cosh ^{2} r-2 \cosh r \sinh r \cos \phi+\sinh ^{2} r\right)\\ & =\frac{\hbar}{2 m \omega_{0}}(\cosh 2 r-\sinh 2 r \cos \phi) \\ (\Delta p)^{2}_{re^{i\phi},0} & =\frac{\hbar m \omega_{0}}{2}(\cosh 2 r+\sinh 2 r \cos \phi). \end{aligned}\]
Let \(\phi=0\), then \[\begin{aligned} \cosh 2 r+\sinh 2 r & =e^{2 r}\quad\text{and}\quad \cosh 2 r-\sinh 2 r & =e^{-2 r} \end{aligned}\] and \(\Delta x\) is squeezed by \(e^{-r}\) while \(\Delta p\) is expanded by \(e^{r}\).
Change \(\phi \rightarrow \pi\) and
it is reversed!
The product of the uncertainties are unchanged, but we have a trade off
from \(x\) to \(p\) and vice versa.
You will explore this more thoroughly on the homework.
The last topic we will cover is how to determine the squeezed states
themselves. To do this, we need to recall the work from HW \(\# 1\) on the symplectic group. We saw that
\[\left[\hat{K}_{0}, \hat{K}_{\pm}\right]=
\pm \hat{K}_{ \pm} ~\text {and }~\left[\hat{K}_{+},
\hat{K}_{-}\right]=-2 \hat{K}_{0}.\]
Here, we claim \(\hat{K}_{+}=\frac{1}{2}
(\hat{a}^{\dagger})^{2}, \quad \hat{K}_{-}=\frac{1}{2}
\hat{a}^{2}\), and \(\hat{K_{0}}=\frac{1}{4}(\hat{a}^{\dagger}\hat{a}+\hat{a}
\hat{a}^{\dagger})\).
Check:
\[\begin{aligned} \left[\hat{K}_{+},\hat{K}_{-}\right] & =\frac{1}{4}\left[(\hat{a}^{\dagger})^{2}, \hat{a}^{2}\right] \\ & =\frac{1}{4}\left[\hat{a}^{\dagger}\left[\hat{a}^{\dagger}, \hat{a}^{2}\right]+\left[\hat{a}^{\dagger}, \hat{a}^{2}\right] \hat{a}^{\dagger}\right) \\ & =\frac{1}{4}\left(\hat{a}^{\dagger}\left(\hat{a}\left[\hat{a}^{\dagger}, \hat{a}\right]+\left[\hat{a}^{\dagger}, \hat{a}\right) \hat{a}\right)+\right. \left.\left(\hat{a}\left[\hat{a}^{\dagger}, \hat{a}\right]+\left[\hat{a}^{\dagger}, \hat{a}\right] \hat{a}\right) \hat{a}^{\dagger}\right) \\ & =-\frac{1}{2}\left(\hat{a}^{\dagger}\hat{a}+\hat{a} \hat{a}^{\dagger}\right) \checkmark \\ \left[\hat{K}_{0}, \hat{k}_{+}\right] & =\left[\frac{1}{4}\left[\hat{a}^{\dagger} \hat{a}+\hat{a} \hat{a}^{\dagger}\right), \frac{1}{2} (\hat{a}^{\dagger})^{2}\right] =\frac{1}{8}\left(\hat{a}^{\dagger}\left[\hat{a}, (\hat{a}^{\dagger})^{2}\right]+\left[\hat{a}, (\hat{a}^{\dagger})^{2}\right] \hat{a}^{\dagger}\right) \\ & =\frac{1}{8}\left(2 \hat{a}^{\dagger} \hat{a}^{\dagger}+2 \hat{a}^{\dagger} \hat{a}^{\dagger}\right)=\frac{1}{2} (\hat{a}^{\dagger})^{2} \checkmark \\ \left[\hat{K}_{0}, \hat{K}_{-}\right] & =\left[\frac{1}{4}\left(\hat{a}^{\dagger}\hat{a}+\hat{a} \hat{a}^{\dagger}, \frac{1}{2} \hat{a}^{2}\right]=-\frac{1}{2} \hat{a}^{2} \checkmark\right. \end{aligned}\]
So we can immediately use the result from the exponential disentangling identity for the symplectic group \[\begin{aligned} & \exp \left[-\xi \hat{K}_{+}+2 i \eta \hat{K}_{0}+\xi^{*} \hat{K}_{-}\right] =e^{-\frac{\lambda}{\kappa^{*}} \hat{K}_{+}} e^{-2 \ln \kappa^{*} \hat{K}_{0}} e^{\frac{\lambda^{*}}{\kappa^{*}} \hat{K}_{-}} \end{aligned}\] So, for us, we have \(\hat{S}(\xi, \eta)=e^{-\frac{\lambda}{2 k x} (\hat{a}^{\dagger})^{2}} e^{-2\ln \kappa^{*} \frac{1}{4}(\hat{a}^{\dagger} \hat{a} + \hat{a}\hat{a}^{\dagger})} e^{\frac{\lambda}{2\kappa^{*}} \hat{a}^{2}}\) then the squeezed vacuum (for the special case \(\xi=r e^{i \phi}, \quad \eta=0, \quad \kappa = \cosh r, \quad \text{and}\quad\lambda=e^{i \phi} \sinh r\)) becomes \[\begin{aligned} & S\left(r e^{i \phi}, 0\right)|0\rangle=e^{-\frac{e^{i \phi}}{2} \tanh r\left(\hat{a}^{\dagger}\right) ^2} e^{-\frac{2}{4} \ln (\cosh r)\left(\hat{a}^{\dagger}\hat{a}+\hat{a} \hat{a}^{\dagger}\right)} \underbrace{e^{\frac{e^{i \phi}}{2} \tanh (\hat{a})^{2} } }_{\text{goes to 1}}|0\rangle \\ & \left.\left.\left(\hat{a}^{\dagger} \hat{a}+\hat{a}\hat{a}^{\dagger}\right) |0\rangle=1 \cdot |0\right\rangle=|0\right\rangle \\ & \boxed{ S\left(r e^{i \phi}, 0\right) |0\rangle=\frac{1}{\sqrt{\cosh r}} \exp \big(-\tfrac{1}{2} e^{i \phi } \tanh r (\hat{a}^{\dagger})^{2}\big)} \end{aligned}\]
Hence, the normalized squeezed vacuum is \[\boxed{ S(re^{i \phi},0)|0\rangle =\frac{1}{\sqrt{\cosh r}} \sum_{m=0}^{\infty}\left(-\frac{1}{2} e^{i \phi} \tanh r\right)^{m} \frac{\sqrt{(2 m)!}}{m!}|2 m\rangle }\]
One can also look at the displaced squeezed state (note one can squeeze then displace or vice versa): \[\hat{D}(\alpha) \hat{S}(\xi, \eta)|0\rangle\] or \[\hat{S}\left(\xi^{\prime}, n^{\prime}\right) \hat{D}(\alpha^{\prime})|0\rangle.\] These states are NOT, in general, equal to each other, but we can find the mapping \[\xi \rightarrow \xi^{\prime} \quad \eta \rightarrow \eta^{\prime} \text { and } \alpha \rightarrow \alpha^{\prime}\] that corresponds to the same state. It is likely to be messy.
Note finally that time dependence of these states is simple due to
braiding, so \[e^{-i \frac{\hat{H} t}{\hbar}}
\hat{S}(\xi, \eta)|0\rangle=e^{-i \frac{\omega_{0} t}{2}}
\hat{S}\left(\xi e^{-\alpha i \omega t}, \eta\right)|0\rangle.\]
We have \(\xi\) changes periodically
with time, but \(\eta\) does not,
because \([\hat{H},
\hat{a}^{\dagger}\hat{a}]=[\hat{H}, \hat{a}
\hat{a}^{\dagger}]=0\). So those operators are constants of the
motion. This implies \(\eta\) remains
constant!
One interesting question is how do we create coherent and squeezed
states? In general, it is not so simple. For light, we will find all
classical sources of light are coherent states. Squeezing light takes a
fair amount of work involving nonlinear optics. This is true about other
systems as well. One has to work with a strategy to make such states. It
is not so simple (of course the same is true for energy eigenstates
\(\cdots\)).
We can also squeeze and displace excited states, but that ends up not
being very useful.
The squeezed vacuum plays an important role in improving the accuracy of
LIGO, as we will see when we discuss it later in the class. It can make
a significant improvement in the accuracy of the measurements.